Delivering health programs for Aboriginal and Torres Strait Islander children: Carer and staff views on what's important. (17th June 2022) - Chando, Shingisai; Dickson, Michelle; Howell, Martin; Tong, Allison; Craig, Jonathan C.; Slater, Kym; Smith, Natalie; Nixon, Janice; Eades, Sandra J.; Howard, Kirsten
Abstract: Background: The lack of evidence on the priorities of carers and their Aboriginal and Torres Strait Islander children undermines decisions to improve participant experiences and engagement. Aims: This study describes carer and staff perspectives on the aspects of health services delivery that are important to carers and children. Methods: Nineteen carers of Aboriginal and Torres Strait Islander children and 17 staff who work at child health programs across two urban Aboriginal Community Controlled Health Services (ACCHSs) and affiliate organisations in New South Wales, Australia participated in semi‐structured interviews. We used thematic analysis to analyse the data. Results: We identified five themes: valuing relational communication (building trust by keeping relationships at the centre, empowered to optimise child's development, feeling heard and known); confidence in provider's clinical and interpersonal skills (certain that the health issue will be resolved, engaging with the child to allay fears, facilitating timely health care); finding comfort and security in community embedded services (safety and acceptance in the familiar, strengthening child's connection to culture); support to access and navigate health services (accessible information appropriately presented, easy and flexible scheduling, easing the shame of financial hardship); sustaining service use (fulfilling expectations for service standards, demonstrating commitment through ongoing programs, clarity of benefits). Conclusions: Carers and staff reported that approaches to communication, the content of that communication, how access is facilitated and the service environment managed influences their decisions to interact with health services. With these data decision‐makers can better focus resources to improve experiences with their services.